New data on the ecological peculiarities and the distribution in Bulgaria of the vulnerable habitat F3.1d Balkan-Anatolian submontane genistoid scrub from the European Red List of Habitats - Kunev Georgi (Hacquetia, 2019)
The study presents new data on the habitat dominated by the species complex of Genista lydia/G. rumelica in Bulgaria. It is based on 129 phytocoenological relevés and provides information on the chorology, ecology and floristic structure of these communities. This habitat type occupies substrates composed by different volcanic rocks. The floristic structure is very rich in species. The phytogeographical relationships with the East Mediterranean region are considerable, which is proved by the high occurrence of floristic elements with Mediterranean or sub-Mediterranean origin. The plant life-forms analysis demonstrates that the therophytes, geophytes and chamephytes prevail in their floristic structure, which is also typical for the shrub communities in this region. During the field study this vegetation type has been mapped and its total area of occupancy has been calculated. For a first time it is proposed this habitat to be divided into three habitat sub-types due to the established differences in the environmental factors. Some recommendations have been proposed on the conservation management and also complements on the habitat‘s descriptions in EUNIS habitat classification.